The Analysis of Concept Mastery Using Redox Teaching Materials with Multiple Representation and Contextual Teaching Learning Approach (Jurnal Pendidikan IPA Indonesia, 2019)
Teaching materials are one of the supportive facilities in achieving successful learning. This study employed teaching materials characterized by Multiple Representations and Contextual Teaching Learning. This research intended to reveal the understanding of redox concepts taught in grade X. This study was an implementation of the results referring to the 4D (Define, Design, Develop, and Disseminate) model. The data collection methods adopted were observation, questionnaire, test, and documentation. The data was analyzed by using the descriptive-qualitative method. The teaching materials have been declared valid, practical, and useful. The users also gave a positive response to the teaching materials. Students’ conceptual understanding was analyzed through each item and indicator. The overall students’ concept mastery was 53.33%, and their understanding of each indicator was 50.214% for interpreting, 77.78% for exemplifying, 53.472% for classifying, 52.78% for guessing, 52.78% for comparing, and 62.5% for explaining.